2002
DOI: 10.2224/sbp.2002.30.5.485
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics as Predictors of Teacher-Student Relationships: Stress, Negative Affect, and Self-Efficacy

Abstract: Students' misbehavior has been consistently linked to teachers' reports of stress. The purpose of this study was to investigate whether or not teacher stress, negative affect, and self-efficacy predict the quality of student-teacher relationships. Participants included 113 elementary (K-5th) teachers in a metropolitan area in the United States. A survey method was used to measure teacher perceptions in working with difficult students and their relationships with students. Negative teacher-student relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
208
1
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(253 citation statements)
references
References 19 publications
5
208
1
25
Order By: Relevance
“…Indeed, the teachers were between 16 to 20 years job experiences that got the higher scores on teacher efficacy in comparison with other groups. These findings are consistent with previous studies which found that for example, female, married teachers had higher levels of wellbeing and self efficacy (BRIDGWATER, 1982;CHEN, 2003;CHEN-YI HOU, 2007, CURTIS;LIYING, 2001;ENTWISTLE, 1987;FISLER;FIRESTONE, 2006;HUGHES et al, 1988;MUIJS;REYNOLDS, 2005;MULLINS, 1992;NODDINGS, 2005;ONAFOWORA, 2005;POLK, 2006;POST, 2005;QI LI-LI, 2009;ROGALLA, 2004;SELIGMAN, 2002;YOON, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the teachers were between 16 to 20 years job experiences that got the higher scores on teacher efficacy in comparison with other groups. These findings are consistent with previous studies which found that for example, female, married teachers had higher levels of wellbeing and self efficacy (BRIDGWATER, 1982;CHEN, 2003;CHEN-YI HOU, 2007, CURTIS;LIYING, 2001;ENTWISTLE, 1987;FISLER;FIRESTONE, 2006;HUGHES et al, 1988;MUIJS;REYNOLDS, 2005;MULLINS, 1992;NODDINGS, 2005;ONAFOWORA, 2005;POLK, 2006;POST, 2005;QI LI-LI, 2009;ROGALLA, 2004;SELIGMAN, 2002;YOON, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that experiences of high teacher-student conflict could undermine teachers' efficacy beliefs and evoke feelings of helplessness. Similarly, the percentage of teacher-student relationships in the classroom judged as negative by the teacher has been found to be associated with teacher reports of stress and negative emotions (Yoon 2002). In contrast, Mashburn et al (2006) found that it was closeness, and not conflict, that was positively related to teachers' efficacy beliefs regarding management of difficult child behavior in a sample of pre-kindergarten teachers.…”
Section: The Influence Of Teacher-student Relationships On Teacher Wementioning
confidence: 97%
“…Steps R self-task (anxiety)-and other (irritation, nervousness)-related negative emotions than the rest of the emotions, indicating the determinant role of the significant others, such as school administration, students and colleagues in their well being (see Buss & Hughes, 2007;Frenzel et al, 2009;Lambert et al, 2009;McCormick & Barnett, 2011;Parrrott, 2003;Schutz, Hong, Cross, & Osbon, 2006;Summers & Davis, 2006;Yoon, 2002). It should mentioned that high anxiety can impairs task relevant processing, such as solving the various problems that occur every day in school (Ashcraft & Kirk, 2001;Schutz & DeCuir, 2002).…”
Section: Emotionsmentioning
confidence: 99%